Accuracy of the Full Spectrum Endoscopy (FUSE) system for assessment of disease activity in Inflammatory Bowel Diseases (IBD) compared to high-definition endoscopy - Heinz Albrecht; Michael Vieth; Gian Eugenio Tontini; Helmut Neumann (Archives of Clinical Gastroenterology - Peertechz Publications, 2019)
Introduction: Recently, Full Spectrum Endoscopy (FUSE) was introduced as a novel colonoscopy platform. In contrast to other endoscopy systems illumination with the FUSE system is achieved by Light-Emitting Diodes (LEDs) and not by a xenon light source. Currently, the FUSE-system does not provide high-definition imaging yet. In patients with IBD, precise assessment of disease activity (i.e. mucosal healing) is of paramount importance to predict disease outcome and to guide therapy. Aims: To determine in a comparison study whether FUSE has the potential to assess disease activity in patients with IBD in comparison to a matched cohort of patients undergoing High-Definition White-Light Endoscopy (HD-WLE). Materials & methods: Consecutive patients with IBD (n=34) undergoing FUSE colonoscopy were matched to patients with IBD undergoing HD-WLE at the same endoscopy unit. The mucosal vascular pattern and any mucosal abnormalities were recorded. Inflammation in ulcerative colitis was recorded according to Mayo Ulcerative Endoscopic Score (MUES) and in Crohn´s disease according to Crohn´s Disease Endoscopic Index of Severity (CDEIS). Subsequent to endoscopic characterization targeted biopsies were obtained for histopathological analysis of disease activity. Results: 90 cases were included. Mean age of patients was 37 years (Range 18 to 72 years). 59% of patients had diagnosis of Crohn's disease and 41% diagnosis of ulcerative colitis. Accuracy of FUSE and HD-WL endoscopy for diagnosis of disease activity in IBD was not statistically significant different (83.8% versus 71.7%). The PPV and NPV for FUSE and HD-WLE did not differ significantly. In the subgroup analysis FUSE and HD-WLE endoscopy yielded in underdiagnosis and overdiagnosis of disease activity in 57% versus 46% and 43% versus 54% of not correctly predicted cases, respectively. Overall, FUSE was more accurate for diagnosis of disease activity in Crohn's disease patients, while HD-WL endoscopy was more accurate for diagnosis of disease activity in ulcerative colitis. Conclusion: Despite the use of LEDs resulting in a darker image and high-resolution imaging, the FUSE seems to be equally effective to high-definition white-light imaging for diagnosis of disease activity in patients with IBD.